Living Inside a Jellyfish: The Symbiosis Case Study of Host-Specialized Dinoflagellates, “Zooxanthellae”, and the Scyphozoan Cotylorhiza tuberculata - Enrique-Navarro, Angélica; Huertas, Emma; Flander-Putrle, Vesna; Bartual, Ana; Navarro, Gabriel; Ruiz, Javier; Malej, Alenka; Prieto, Laura (Frontiers in Marine Science, 2022)
The photosymbiosis with host-specific dinoflagellates is a widespread relationship in marine organisms. Despite the evidenced biodiversity of this kind of mutualism, most research focuses on the study of scleractinian corals, and there is a lack of knowledge about other symbiotic cnidarians such as jellyfishes. The Mediterranean jellyfish Cotylorhiza tuberculata (Rhizostomae, Scyphozoa) harbors an endosymbiotic dinoflagellate of the family Symbiodiniaceae. In this study, we examine the algae distribution within the host body as well as, the pigment content and cell density of the symbiont. Furthermore, the size, morphology and fluorescence of cultured symbionts were studied under light microscopy, Imaging Flow Cytometry (IFC), and Scanning Electron Microscopy (SEM). The C:N composition and optical properties of the medusa tissue were measured to evaluate their role in the symbiosis. The medusae body was divided into two different sections to investigate the distribution of symbionts in hospite: oral arms (OA) and umbrella (UM). C:N composition of C. tuberculata was and symbiont density was significantly higher in the OA section. Mean chlorophyll a concentration of the algae was 1.33 (± 0.83) pg Chl a cell-1. The study of the pigment composition by HPLC (High Performance Liquid Chromatography), revealed the presence of 13 different pigments, being the most representative chlorophyll a, chlorophyll c2, and peridinin typical pigments of Symbiodiniaceae. Cell diameter of algae freshly isolated from the host was 8.71 ± 0.97 μm and cell growth rate was 0.52 (± 0.09) 106 cell ml-1 d-1. The presence of vegetative coccoid cells, doublet and motile mastigotes were revealed within the Symbiodiniaceae cultures. A calcifying matrix typical of Symbiodiniaceae and formed in partner with bacteria, was also observed most cultures. The umbrella tissue of the medusa absorbed at ultraviolet radiation (UVR) region, suggesting that medusae tissue protects photosymbionts from the negative effect of the high energetic UVR and attenuates the light intensity reaching algae inside the host. The presence of a dense Symbiodiniaceae population and the protection to UVR and elevated environmental irradiance provided by medusae tissue, maintain symbionts in optimal light conditions for photosynthesis and may be a reason added to explain the population success of Cotylorhiza tuberculata.